Suzuki-Type Generalization of Chatterjea Contraction Mappings on Complete Partial Metric Spaces. (12th June 2013) - Imdad, Mohammad; Erduran, Ali
Abstract : Motivated by Suzuki (2008), we prove a Suzuki-type fixed point theorem employing Chatterjea contraction on partial metric spaces.